Penguatan Kompetensi Digital Dan Kesiapan Kerja Lulusan Muda Melalui Pelatihan Koding Dan Kecerdasan Artifisial - Fatihanursari Dikananda; Cep Lukman Rohmat; Anggun Riani; Sifaul Qulub (CV. Multi Kreasi Media, 2026)
This program aims to improve digital literacy, coding skills, the use of Artificial Intelligence, and student job readiness to face the development of digital technology-based industries. The background of the activity is based on the need to improve the digital competence of the younger generation in the era of industrial transformation 4.0. The development of digital technology and Artificial Intelligence has resulted in the world of work requiring human resources who have the ability to adapt to technology, think critically, creatively, and are able to utilize technology productively. However, some students still have limited understanding of coding and the use of AI. The implementation method of the activity uses an educational, participatory approach and direct practice through coding workshops and Artificial Intelligence training. Participants received materials on digital literacy, basic algorithms, programming logic, the use of AI tools, digital technology ethics, and motivation for job readiness. The results of the activity showed that participants experienced an increased understanding of coding and Artificial Intelligence. Participants were able to understand the basic concepts of simple programming and the use of AI to support digital learning and productivity. In addition, the activity also increased motivation to learn technology and participant job readiness. Evaluation of the activity implementation showed a high level of participant satisfaction with the quality of the material, training methods, the competence of the speakers, and the benefits of the workshop. The community service activity also strengthened cooperation between universities and SMKN 1 Cirebon in supporting the development of digital technology-based vocational education. Overall, this community service program has successfully made a positive contribution to improving the digital competency and job readiness of young graduates through coding and Artificial Intelligence training.